2019
DOI: 10.7554/elife.48410
|View full text |Cite|
|
Sign up to set email alerts
|

A nuclear role for the DEAD-box protein Dbp5 in tRNA export

Abstract: Dbp5 is an essential DEAD-box protein that mediates nuclear mRNP export. Dbp5 also shuttles between nuclear and cytoplasmic compartments with reported roles in transcription, ribosomal subunit export, and translation; however, the mechanism(s) by which nucleocytoplasmic transport occurs and how Dbp5 specifically contributes to each of these processes remains unclear. Towards understanding the functions and transport of Dbp5 in Saccharomyces cerevisiae, alanine scanning mutagenesis was used to generate point mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 79 publications
4
19
0
Order By: Relevance
“…Our data and our resulting model are consistent with a recent report that defined the nuclear export signal (NES) for Dbp5 and concluded that nuclear shuttling is not essential for mRNA export [33]. The discovery of an NES in Dbp5 establishes that nuclear export of Dbp5 itself is not dependent on mRNA export, in agreement with the lack of nuclear Dbp5 enrichment observed in rat7-1 and gle1-4 mutants (Fig 1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data and our resulting model are consistent with a recent report that defined the nuclear export signal (NES) for Dbp5 and concluded that nuclear shuttling is not essential for mRNA export [33]. The discovery of an NES in Dbp5 establishes that nuclear export of Dbp5 itself is not dependent on mRNA export, in agreement with the lack of nuclear Dbp5 enrichment observed in rat7-1 and gle1-4 mutants (Fig 1).…”
Section: Discussionsupporting
confidence: 92%
“…Given the recently described nuclear role for the human Dbp5 homologue DDX19B [32] and the suggested function for Dbp5 during tRNA processing in the nucleus [33], a more detailed knowledge of Dbp5's mode and site(s) of interaction with the mRNP is critical to understanding Dbp5 functions. In this study, we present several lines of evidence that Dbp5 association with the mRNP prior to export is not required for its remodeling activity at the NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single molecule and polyA-RNA FISH was performed as described in ( 81 , 82 ), with the exception that smiFISH probes were used to detect gene transcripts by single molecule FISH ( 83 ). At indicated time points, ∼3.5 OD of meiotic cultures was fixed with 37% formaldehyde for 20 min at room temperature followed by overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Dbp5 is localized in the nucleus, in the cytoplasm and concentrated around the nuclear rim [27,32]. A nuclear export signal and a nuclear import signal were identified in the N-terminus of the protein, enabling shuttling between the compartments [33]. The helicase core of Dbp5 is composed of two highly conserved RecA-like domains linked by a hinge region [34].…”
Section: The Function Of Dbp5 In Translation Terminationmentioning
confidence: 99%